Dinamika Pekarangan Kampung Selahuni 2, Desa Ciomas Rahayu, Bogor - Muhammad Saddam Ali; Hadi Susilo Arifin; Nurhayati H.S. Arifin (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Urbanization and fragmentation are the main factors causing dynamics in the pekarangan. The dynamics that occur are related to the structure and function of the pekarangan. This makes the pekarangan performance changes according to the interference of the pekarangan owner. Selahuni 2 Homlet, Ciomas Rahayu Village, Bogor has become the location for observing the dynamics of the past two decades. Pekarangan samples taken in 2019 are exactly the same as those taken in 1998 and 2007, totaling 10 houses. The aim is to determine the extent of changes that occur in the pekarangan, both structure and function. Measuring the area, ownership of the pekarangan, recording of species and function of the existing vegetation of the pekarangan. In 2019, data on ownership of houses and pekarangans by old owners dropped dramatically by only 40%. In 2019, the average pekarangan area will decrease by an average area of 110.81 m2. In 1998, 2007 and 2019, the percentage of the number of non-ornamental plant species was 4-10% higher than that of ornamental plants. Therefore, there was a change in both the extent and ownership, function and structure of the vegetation in the Selahuni 2 Homlet’s pekarangan which was caused by urbanization and fragmentation factors.